2014
DOI: 10.1016/j.wombi.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

A meta-ethnographic study of health care staff perceptions of the WHO/UNICEF Baby Friendly Health Initiative

Abstract: Findings: Three overarching themes were identified. First the BFHI was viewed variously as a 'desirable innovation or an unfriendly imposition'. Participants were passionate about supporting breastfeeding and improving consistency in the information provided. This view was juxtaposed against the belief that BFHI represents an imposition on women's choices, and is a costly exercise for little gain in breastfeeding rates. The second theme highlighted cultural and organisational constraints and obstacles to BFHI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
4
18
1
Order By: Relevance
“…Another Australian study also identified national breastfeeding statements as 'soft' policy due to the lack of tangible incentives or measurable outcomes [21,40]. In regards to establishing a BFHI culture, recent literature has also identified the impact of leadership support at the government [40] and organisational levels on the uptake and implementation of the BFHI [37,41] via providing required resources as enablers [42] while 'intangible government support' and 'suboptimal capacity building' and resource issues flag barriers [21,25,43]. Other barriers to the successful establishment of the BFHI culture are difficulties associated with changing existing practices of hospitals [37] or resistance to new policies [43] and therefore, a change in practice and attitude by staff is required [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another Australian study also identified national breastfeeding statements as 'soft' policy due to the lack of tangible incentives or measurable outcomes [21,40]. In regards to establishing a BFHI culture, recent literature has also identified the impact of leadership support at the government [40] and organisational levels on the uptake and implementation of the BFHI [37,41] via providing required resources as enablers [42] while 'intangible government support' and 'suboptimal capacity building' and resource issues flag barriers [21,25,43]. Other barriers to the successful establishment of the BFHI culture are difficulties associated with changing existing practices of hospitals [37] or resistance to new policies [43] and therefore, a change in practice and attitude by staff is required [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recent Australian studies, including our own study, have identified barriers and facilitators related to the uptake and implementation of the BFHI at both macro and micro levels [21,24,25]. Examples of barriers to successful uptake and implementation in Australia are cultural and organisational obstacles [25], intangible government support, suboptimal capacity building to implement the BFHI [21,25], and lack of established legal measures to implement the WHO Code [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to consider further research questions related to actual implementation of the revised BFHI to update existing knowledge (Pérez‐Escamilla et al, ; Schmied et al, ). Recognizing that scaling up breastfeeding takes place in a complex adaptive world (Pérez‐Escamilla & Hall Moran, ), we could use ecological perspectives to further explore the ways in which change in relation to the revised BHFI is managed at a macro (society level), meso (community level), and micro (individual level; McLaren & Hawe, ).…”
Section: Monitoring and Learning From Implementationmentioning
confidence: 99%
“…It is important to consider further research questions related to actual implementation of the revised BFHI to update existing knowledge Schmied et al, 2014). Recognizing that scaling up breastfeeding takes place in a complex adaptive world (Schmied, Beake, Sheehan, McCourt, & Dykes, 2011) and prioritizing relationships to better facilitate mothers' capacities to respond to their babies' cues (Dykes & Flacking, 2010;Thomson, Bilson, & Dykes, 2012).…”
Section: Monitoring and Learning From Implementationmentioning
confidence: 99%